Four years’ maternal mortality updates of a high referral burden teaching hospital of Eastern Uttar Pradesh, India - Saxena, Riden; Jain, Madhu; Rani, Anjali (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2018)
Background: Maternal mortality is still a major challenge in developing countries but in our hospital, it touches the extreme height of MMR. The target of the study is to assess the cause of maternal mortality at Sir Sunder Lal Hospital, Banaras Hindu University, Varanasi, India. Methods: Data collection was done from the patient maternal mortality records of hospital between 2013 to 2016. Study comprises only maternal mortality cases. Total 165 maternal deaths were included in this study. Results: Maternal mortality ratio is extremely high as compare to other studies. In an increasing trend, in the year 2015 MMR was highest. Moreover, we found direct causes accounted 77.5% of total maternal deaths Hypertensive disorders and eclampsia is the most frequent cause of deaths which represented 33.3%. We found a trend of increased MMR with Increased unbooked cases. 21.2% of total dead women couldn’t get beds in ICU because of not vacancy of beds and 18.8% of total women died due to non-affordability of ICU expenses. Conclusions: Our hospital is a high burden referral apex centre of eastern Utter Pradesh in India which experience mostly referred cases from the periphery. PPH and hypertensive disorder are two major causes which lead to deaths. Cardiovascular dysfunction is most accounted for deaths. Mostly patients were needed ventilatory support to survive but lack of separate ICU and improper antenatal visits leads to MMR higher. However, many other factors like ill-literacy, poor transportation, poor referral note, poor socio-demographic status should be dealt to incline the MMR.